Effectiveness of steam cleaning technology on reducing the occurrence of ESKAPE organisms and Escherichia coli in the stables of an equine referral hospital - S. Sosa-Portugal; L. Dale; J. Devaney; A. Sharp; F. Malalana; D. Timofte (Journal of Equine Veterinary Science, 2025)

The development, validation and application of an indirect enzyme-linked immunosorbent assay (ELISA) for the detection of antibodies to Streptococcus dysgalactiae subspecies dysgalactiae in lamb and ewe sera - L.P. Jackson; D. Timofte; K.T. Ballingall; J.S. Duncan (Research in Veterinary Science, 2025)

A multinational survey of companion animal veterinary clinicians: How can antimicrobial stewardship guidelines be optimised for the target stakeholder? - S. Farrell; A.F. Bagcigil; S.C. Chaintoutis; C. Firth; F.G. Aydin; C. Hare; M. Maaland; A. Mateus; A.P. Vale; U. Windahl; P. Damborg; D. Timofte; et al. (The Veterinary Journal, 2024)

Concept of Suicide: Neurophysiological/Genetic Theories and Possible Oxytocin Relevance - M. Padurariu; R. Prepelita; A. Ciobica; R. Dobrin; D. Timofte; C. Stefanescu; R. Chirita (Neurophysiology, 2016)

Emergence of concurrent infections with colistin-resistant ESBL-positive Klebsiella pneumoniae and OXA-23-producing Acinetobacter baumannii sensitive to colistin only in a Romanian cardiac intensive care unit - D. Timofte; M. Dan; I. E. Maciuca; L. Ciucu; E. R. Dabija; E. Guguianu; C. V. Panzaru (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Intercomparison of five nets used for mesozooplankton sampling - D. ALTUKHOV; I. SIOKOU; M. PANTAZI; K. STEFANOVA; F. TIMOFTE; A. GUBANOVA; A. NIKISHINA; E. ARASHKEVICH (Mediterranean Marine Science, 2015)
Intercomparison of nets commonly used for mesozooplankton sampling in the Black and Mediterranean seas was attempted within SESAME (Southern European Seas: Assessing and Modelling Ecosystem Changes) project. Five nets were compared: three Juday nets equipped with 150 μm, 180 μm and 200 μm mesh size, Nansen net (100 μm mesh size) and WP2 (200 μm mesh size). Replicated samples were collected at one station in the western Black Sea offshore waters in April 2009. Collected samples were analyzed at species level (except for meroplankton), stages (for copepods) and size length. A decrease of total abundance values was observed with increasing mesh size, due to the significantly higher numbers of animals smaller than 1 mm in the samples obtained by fine mesh size than with coarser nets. Few comparisons were revealed significant for the abundance of animals with 1-2 mm length, while no significance was detected for specimens larger than 2 mm. The above differences resulted in discripancies between nets regarding species and stages composition. Biomass values did not differ significantly between nets, due to the strong contribution to total biomass of the large animals fraction (Calanus euxinus). The smallest and the largest animals revealed high variability between replicates collected by Nansen, Juday- 200 μm and WP2 nets. Correction factors were calculated for the conversion of abundance values between each couple of nets. The detected differences between nets regarding the abundance and biomass, the community taxonomic composition and size structure, as well as the estimated correction factors, provide useful information for the harmonization of data obtained by the above nets in the Black Sea.